52=c-46

Simple and best practice solution for 52=c-46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 52=c-46 equation:


Simplifying
52 = c + -46

Reorder the terms:
52 = -46 + c

Solving
52 = -46 + c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1c' to each side of the equation.
52 + -1c = -46 + c + -1c

Combine like terms: c + -1c = 0
52 + -1c = -46 + 0
52 + -1c = -46

Add '-52' to each side of the equation.
52 + -52 + -1c = -46 + -52

Combine like terms: 52 + -52 = 0
0 + -1c = -46 + -52
-1c = -46 + -52

Combine like terms: -46 + -52 = -98
-1c = -98

Divide each side by '-1'.
c = 98

Simplifying
c = 98

See similar equations:

| x(x+8)-(25x+3x)=0 | | (-7+9i)+(2-10i)= | | -3x-2y+z=11 | | 6x-77+7x+11=4x-60+3x | | 12x-45=26-3x-4 | | 5x^2+2c+7=0 | | r-46=15 | | 6x-77-7x+11=4x-60-3x | | 30=3v | | x=3-1y | | 7=56j | | 750-50x=-185 | | 2ln(7x)=5 | | y-4.1=5.4 | | a^2+12a-21=0 | | X+(11)=13 | | 3b-5=-44 | | 42x^2-18x= | | ln(5+3)=ln(5)+ln(3) | | E-14=0 | | 21=b-6 | | c+7=9 | | y=20(.682) | | y=20(1.025) | | a+4=35 | | 8(1-3x)=7(3x-1) | | x^2-mx-(m^2-5)=0 | | 4y-9=11y-23 | | (5-2i)-(3+3i)= | | y=95+15x | | -x+b=2 | | 4x-5x-7=3x+10 |

Equations solver categories